More to feed and meat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Want to evaluate the impact of livestock on the environment, or identify technical, institutional or policy options to enhance positive livestock-environment interactions, or mitigate negative impact? The new FAO Internet toolbox can help. For...